\(\frac{1}{29}\).x2-4y2-4xy
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(x^4+2x^2+1-x^2\)
= \(\left(x^2+1\right)^2-x^2\)
= \(\left(x^2+x+1\right)\left(x^2-x+1\right)\)
b, \(x^4+x^2+1\)
= \(x^4+2x^2+1-x^2\)
= .. ( như phần a )
c, \(y^4+64\)
= \(\left(y^2+8\right)\left(y^2-8\right)\)
d, \(4xy+3z-12y-xz\)
\(=4y\left(x-3\right)-z\left(x-3\right)\)
\(=\left(x-3\right)\left(4y-z\right)\)
e, \(x^2-4xy+4y^2-z^2+6z-9\)
\(=\left(x-2y\right)^2-\left(z-3\right)^2\)
g, \(x^2-4xy+5x+4y^2-10y\)
\(=\left(x^2-4xy+4y^2\right)+\left(5x-10y\right)\)
\(=\left(x-2y\right)^2+5\left(x-2y\right)\)
\(=\left(x-2y\right)\left(x-2y+5\right)\)
h, \(x^2-7x+6\)
\(=x^2-6x-x+6\)
\(=x\left(x-6\right)-\left(x-6\right)\)
\(=\left(x-6\right)\left(x-1\right)\)
i, \(x^3+5x^2+6x+2\)
\(=x^3+x^2+4x^2+4x+2x+2\)
\(=x^2\left(x+1\right)+4x\left(x+1\right)+2\left(x+1\right)\)
\(=\left(x+1\right)\left(x^2+4x+2\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Lời giải:
$x^2+y^2+4xy+4y^2-2y=-1$
$\Leftrightarrow (x^2+4xy+4y^2)+(y^2-2y+1)=0$
$\Leftrightarrow (x+2y)^2+(y-1)^2=0$
Ta thấy $(x+2y)^2\geq 0; (y-1)^2\geq 0$ với mọi $x,y\in\mathbb{R}$
Do đó để tổng của chúng bằng $0$ thì $(x+2y)^2=(y-1)^2=0$
$\Leftrightarrow y=1; x=-2$
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^2+4xy-9+4y^2\)
\(=\left(x^2+4xy+4y^2\right)-9\)
\(=\left(x+2y\right)^2-3^2\)
\(=\left(x+2y+3\right)\left(x+2y-3\right)\)
\(=\left(x+2y\right)^2-9=\left(x+2y-3\right)\left(x+2y+3\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^2+4y^2-4xy-4\)
\(=\left(x^2-4xy+4y^2\right)-4\)
\(=\left(x-2y\right)^2-2^2\)
\(=\left(x-2y-2\right)\left(x-2y+2\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x^2+4xy-4z^2+4y^2\)
\(=x^2+4xy+4y^2-4z^2\)
\(=\left(x+2y\right)^2-4z^2\)
\(=\left(x+2y-2z\right)\left(x+2y+2z\right)\)
\(x^2+2x-15\)
\(=x^2+2x+1-16\)
\(=\left(x+1\right)^2-16\)
\(=\left(x+1-4\right)\left(x+1+4\right)\)
\(=\left(x-3\right)\left(x+5\right)\)